Pengaruh Flux Elektroda AWS 5.1 E 6013 Dicelup Oli pada Pengelasan Besi Cor Kelabu FC-25 Terhadap Kekuatan Tarik - Aris Hermanto; Iswanto Iswanto (Universitas Muhammadiyah Sidoarjo, 2018)
In this study using specimens of gray cast iron Fc-25 (grade 2500). The test specimen is needed there 12 specimens include three test specimen material (base metal), 3 specimen variety of welding electrodes cast CI-A1, 3 specimen variety of welding using welding electrodes AWS 5.1 E6013 without immersion oil, three specimens variation welding using welding electrodes 5.1 AWS E6013 with immersion oil. The results of testing specimens welding electrodes cast CI-A1 in the amount of 16.63 MPa with 0.84% strain and a variety of welding electrode AWS E6013 5.1 with immersion oil also has the highest ultimate tensile strength of welding another variation in the amount of 17.98 MPa with a strain of 0.48% , While the lowest was tensile strength using a variety of welding electrode AWS E6013 5.1 without immersion oil that is 16.28 MPa with a strain of 0.49%.